A 100 million year old gecko with sophisticated adhesive toe pads, preserved in amber from Myanmar - Arnold, E. Nicholas; Poinar, George (Zootaxa, 2008)
A new genus and species of gecko is described from a posterior lower limb and foot, and a partial tail, preserved in Lower Cretaceous amber from Myanmar that is 97–110My old. It appears to be the oldest unequivocal fossil gecko, predating fragmentary skeletal remains from the Upper Cretaceous and being 43–56 My older than Yanatarogecko from the Lower Eocene, previously the oldest known gecko preserved in amber. It also provides firm evidence that gekkotans and possibly gekkonids were in Asia at this time. The Myanmar specimen shows, that the distinctive foot proportions and sophisticated adhesive mechanism, involving pads on the toes with transverse lamellae probably bearing numerous hairlike setae found in many modern geckos, had already evolved around 100My ago. The specimen is very small, even compared with juveniles of the smallest living geckos. However, the high numbers of lamellae on its toe pads suggest it is from a juvenile of a species with relatively large adult body size.